2006
DOI: 10.1002/bjs.5179
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of strictureplasty for Crohn's disease

Abstract: Long-term follow-up has confirmed the safety of strictureplasty in Crohn's disease. Morbidity is appreciable, although the surgical mortality rate is low. Reoperation rates are comparable following first and repeat strictureplasty procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
2
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 72 publications
4
37
2
3
Order By: Relevance
“…It has been clearly shown that CD strictures can be treated by strictureplasty instead of resection [19][20][21][22][23][24][25][26] . The regression of inflammatory activity of CD at the strictureplasty site has been well documented by radiological, ultrasonographic, endoscopic or histological investigations [27][28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly shown that CD strictures can be treated by strictureplasty instead of resection [19][20][21][22][23][24][25][26] . The regression of inflammatory activity of CD at the strictureplasty site has been well documented by radiological, ultrasonographic, endoscopic or histological investigations [27][28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…Warunkiem bezpiecznego poszerzenia endoskopowego jest brak owrzodzeń oraz krótki odcinek zwężenia (do 4 cm). Alternatywną metodą jest chirurgiczna plastyka zwężeń [101,102] (zwłaszcza u chorych zagrożonych zespołem krótkiego jelita, ze zwężeniami krótszymi niż 10 cm), a w przypadku długiego odcinka lub zwężeń wielopoziomowych oraz aktywnych zmian w zwężeniu -resekcja odcinkowa jelita [103]. Chirurgiczna plastyka zwężeń w jelicie grubym oraz wytworzenie zbiornika J-pouch nie są zalecane osób z ChLC.…”
Section: Le Ec Cz Ze En Ni Ie E C Ch Hi Ir Ru Ur Rg Gi Ic Cz Zn Ne Eunclassified
“…No entanto, Lashner 16 questiona essa afirmação, sugerindo que o risco não aumenta simplesmente pela exclusão de alça e, sim, pela presença de alças intestinais com doença ativa por longo tempo, predispondo ao desenvolvimento neoplásico. O fato é que as anuloplastias não parecem predispor ao aparecimento de câncer 21 .…”
Section: Discussionunclassified